The Power Supply Industry Best Practice Manual for Power Generation and Transport, Economics and Trade - Konstantin, Panos (Springer International Publishing, 2018)
Power and Energy industry is a highly capital intensive business field. Furthermore there is a very close interlinkage between technologies and economics that requires engineering consultants, economists and lawyers dealing with investments in this field to have a basic knowledge of the power sector technologies and a common understanding of project evaluation approaches and methodologies. The book's overall objective is to provide a comprehensive but concise coverage of power supply technologies and the related economics as required for techno-economic evaluation of investments in power and business projects. Throughout the book, the emphasis is on transferring practical know-how rather than pure theoretical knowledge. This is also demonstrated in numerous examples derived from experience of respective projects. The book comprises eleven chapters, 35 tables, 100 figures, 35 application examples and 10 case studies Target audience of the book are primarily international consultants, staff members of engineering companies, utility personnel, energy economists and lawyers, as well as employees of government agencies entrusted with regulating the energy and utility sector and, finally, students in related fields of engineering and economics.